Sustainable Strategy for Algae Biomass Waste Management via Development of Novel Bio-Based Thermoplastic Polyurethane Elastomers Composites - Ewa Głowińska; Olga Gotkiewicz; Paulina Kosmela (Molecules, 2023)
This work concerns the waste management method of algae biomass wastes (ABW). For this purpose, we prepared bio-based thermoplastic polyurethane elastomer (bio-TPU) composites. Algae biomass wastes are derived from algal oil extraction of Chlorella vulgaris and from biomass of Enteromorpha and Zostera marina. ABWs were used in the bio-TPUs composites as a filler in the quantity of 1, 5, 10, and 15 wt.%. The bio-based composites were prepared via the in situ method. Polymer matrix was synthesized from a bio-based polyester polyol, diisocyanate mixture (composed of partially bio-based and synthetic diisocyanates), and bio-based 1,3 propanediol. In this study, the chemical structure, morphology, thermal and mechanical properties of prepared composites were investigated. Based on the conducted research, it was determined that the type and the content of algae waste influence the properties of the bio-based polyurethane matrix. In general, the addition of algae biomass wastes led to obtain materials characterized by good mechanical properties and noticeable positive ecological impact by increasing the total amount of green components in prepared bio-TPU-based composites from 68.7% to 73.54%.